Etnomatematika Pada Bentuk Bangunan Keraton Kusuma Negara Di Sekadau Hilir - Riski Suwanto (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Abstract this study is a mathematical study that deals with exploring the application of the concept of ethnomathematics in the design of palace buildings in Sekadau Hilir. Through ethnographic approaches and mathematical analysis, this study aims to understand and describe how local communities use mathematical knowledge in creating unique kraton. The research method used involves the collection of field data through observation, and visual documentation. The collected Data were then analyzed using ethnographic approaches and relevant mathematical concepts. The results of this study revealed that the design of the palace building in Sekadau Hilir reflects the use of geometric patterns, symmetry, and mathematical proportions that are integrated with the local culture and environment. This article also highlights the role of ethnomathematics in respecting and preserving local knowledge and promoting recognition of cultural diversity. The practical implications of this study are to provide insights for designers , architects, and other relevant practitioners to broaden their perspectives in creating designs that relate to cultural and mathematical values. Keywords: Ethnomaematics, geometric patterns.